Physiochemical Characteristics, Provenance, and Dynamics of Sand Dunes in the Arid Hexi Corridor - Zhu, Bing-Qi; Zhang, Jia-Xing; Sun, Chun (Frontiers in Earth Science, 2021)
Dynamic changes of aeolian landforms under changing environments in a middle-latitude desert belt is a typical problem of climate change and related landscape response. It need a comprehensive understanding of the formation mechanisms of dune landforms with the supply of material suitable for aeolian transport and favorable conditions of sediment availability and wind regimes in the region. Based on comprehensive evidences from geomorphological, sedimentological, geochemical, and hydrological analysis, this study discussed the dynamical changes of different dune landforms during the past half century and their provenance in the Hexi Corridor, China. The results show that there are two states of sand dunes movement in the Hexi Corridor in the past half century, dynamic migration and basically stable. The crescent-shaped dunes move the fastest, followed by the chains of barchan dunes. Only the top of the pyramid dunes wigwags, while the parabolic dunes and the longitudinal dunes hardly move forward. The moving speed of sand dunes is positively correlated with the wind speed 5m/s at a yearly scale. The grain size of sand dunes in the western Hexi Corridor is coarser than that in the central-eastern part, and also larger than those in other deserts of northern China and of the world. Different motion modes of saltation, suspension, and creeping are identified between aeolian, alluvial/fluvial and gobi sediments. Dune sands are mainly "sediments of in-situ rising" that originated from alluvial/fluvial/lacustrine deposits of ancient rivers, lakes, and aeolian deposits in the erosion zone of the forelands of the Qilian and Beishan Mountains and the north-neighboring deserts. This reveals a significance interaction between wind and water dynamics in the formation and evolution of aeolian landforms in the arid study area. Sufficient transport capacity is evidenced for both the western and eastern parts of the Hexi Corridor, sufficient sand supply and sand availability, however, is the favorable factor for dune formation in the east part but is the limiting factor for the west.